2010
DOI: 10.1152/jn.01100.2009
|View full text |Cite
|
Sign up to set email alerts
|

Neurons in Area 5 of the Posterior Parietal Cortex in the Cat Contribute to Interlimb Coordination During Visually Guided Locomotion: A Role in Working Memory

Abstract: We tested the hypothesis that area 5 of the posterior parietal cortex (PPC) contributes to interlimb coordination in locomotor tasks requiring visual guidance by recording neuronal activity in this area in three cats in two locomotor paradigms. In the first paradigm, cats were required to step over obstacles attached to a moving treadmill belt. We recorded 47 neurons that discharged in relationship to the hindlimbs. Of these, 31/47 discharged between the passage of the fore- and hindlimbs (FL-HL cells) over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 49 publications
4
47
1
Order By: Relevance
“…Furthermore, the finding that the response observed in both young and older adults involved the whole body may indicate the involvement of a central mechanism. It is well known that in cats, the motor cortex and specifically the corticospinal tract are involved in obstacle avoidance during gait by modifying forelimb elevation according to obstacle characteristics (Drew 1988(Drew , 1993Lajoie et al 2010). Microstimulation of pyramidal tract neurons generated a phase shift in the locomotor patterns in the cat hindlimb (Orlovsky 1972) similar to phase shifts observed in this study.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, the finding that the response observed in both young and older adults involved the whole body may indicate the involvement of a central mechanism. It is well known that in cats, the motor cortex and specifically the corticospinal tract are involved in obstacle avoidance during gait by modifying forelimb elevation according to obstacle characteristics (Drew 1988(Drew , 1993Lajoie et al 2010). Microstimulation of pyramidal tract neurons generated a phase shift in the locomotor patterns in the cat hindlimb (Orlovsky 1972) similar to phase shifts observed in this study.…”
Section: Discussionsupporting
confidence: 81%
“…Prior research using functional magnetic resonance imaging has implicated the posterior parietal cortex in upper-limb reaching (Filimon et al, 2009) and in coordination of left and right wrist movements . In addition, microwire arrays implanted into feline posterior partial and motor cortex during flat ground and precision walking have suggested that visuo-motor integration during locomotion is critically dependent on posterior parietal and motor cortex networks Beloozerova and Sirota, 2003;Drew et al, 2002;Lajoie et al, 2010). In our study, we found (with one exception) that within a given frequency band (alpha, beta, or high-gamma) spectral power fluctuations were synchronous across all four electrocortical domains but were not uniformly significant (i.e.…”
Section: Discussioncontrasting
confidence: 53%
“…In feline posterior parietal cortex Beloozerova and Sirota, 2003;Lajoie et al, 2010) and motor cortex (Armstrong and MarpleHorvat, 1996;Drew, 1993;Drew et al, 2002;Widajewicz et al, 1994) neuronal firing rates exhibit peaks that are synchronized to the gait cycle. These studies suggest that feline posterior parietal cortex likely plays a role in visuo-motor integration during locomotion while motor cortex contributes to gait execution.…”
Section: Introductionmentioning
confidence: 99%
“…In spinal cord, ephrinB3 is a midline axon repellant protein (Kullander et al, 2001b). Elimination of ephrinB3, EphA4, or the adapter protein ␣2-Chimaerin results in aberrant bilaterally projecting spinal interneurons (Kullander et al, 2001a;Yokoyama et al, 2001;Kullander et al, 2003;Beg et al, 2007;Iwasato et al, 2007;Wegmeyer et al, 2007;Asante et al, 2010), many of which are central pattern generator (CPG) components . Instead of an alternating gait during overground and treadmill locomotion, null mutants have a hopping gait (Akay et al, 2006).…”
Section: Introductionmentioning
confidence: 99%